Global banking - Smith, Roy C., 1938-; Walter, Ingo.; DeLong, Gayle (New York ; Oxford : Oxford University Press, 2012)
This text reassesses the continuing transformational process of global banking and finance - its causes, its course, and its consequences. It begins with an overview of the most recent developments and goes on to examine the major dimensions of international commercial and investment banking.
Description based on online resource; title from PDF title page (viewed on Mar. 5, 2012).
Includes bibliographical references and index.
Keywords: Banks and banking, International; Capital market; Competition, International